EFEKTIVITAS UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DALAM MENDUKUNG PEMBANGUNAN EKONOMI DAN PENGEMBANGAN WILAYAH KOTA SURAKARTA - Mayastuti, Anti (PARENTAL, 2013)
Traffic and road transport has a strategic role in supporting development and national integration as part of efforts to promote the general welfare, as mandated in the Constitution of the Republic of Indonesia Year 1945, so it requires a synergistic relationship (synergistic relationship) between the implementation of UU No. 22 Tahun 2009 on Traffic and Transportation with economic development and regional development especially in Surakarta. The Government is obliged to keep the roads safe, orderly and smooth, so as to encourage development in areas of the economy and industry, particularly in the areas of production, consumption and distribution of goods or services, either within or between Surakarta, with the ex-residency of Surakarta, in order to achieve equitable development and its results, economic growth and balanced development of the region.